PEMBERDAYAAN KAUM PEREMPUAN DALAM BETERNAK AYAM DI GMIT GETSEMANI OEBATU - Sance Mariana Tameon; Irene Sondang Ully; Jeni Isak Lele; Semri A. Tampani (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
The limited supply of broiler chickens in Rote has become a business opportunity for the people. Therefore, the community service of the Missiology study program focused on the women of GMIT Getsemani Oebatu to breed the chicken and increase their income. The purpose is to empower the women in economic and spiritual aspects to help them understand their role as agents of God's mission. The action research method was applied with a focus on participatory action research in the mentoring process. It runs in four stages: diagnosing (initial survey using observation and interview), planning the action, taking action (training and mentoring), and evaluating by paying attention to the development process until harvest. The result of the mentoring showed that the women of GMIT Getsemani Oebatu were very enthusiastic about raising chickens and wanted to increase income for the family because of its relatively short period of rearing (one month).